Stress and stability analysis of slewing motion for crawler crane mounted on flexible ground. (November 2019) - Yang, Qingle; Qu, Fuzheng; Yu, Zhiyuan; Xie, Zhengyi
Abstract: The ground deformation causes the increasing of crawler crane side loading, even leads to the boom stress failure or crane tipping failure during slewing motion. This paper established a flexible multibody dynamics simulation model considering the coupling effects of the crane mechanical structure flexibility, ground deformation, and load's dynamic pendulum motion. The model has been verified by analytical model based on Winkler foundation and experimental data. Then the simulation model has been further used to analyze the influence of different foundation modulus, slewing speeds, and lifting heights on the crane boom max stress and the tipping stability. The result offers the slewing speed threshold, which can prevent stress and tipping failures for the crawler crane mounted on flexible ground. The research provides reference for the design and safe operation of crawler cranes. Highlights: Flexible multibody dynamics simulation model is established for a crawler crane mounted on flexible ground. Analytical model based on Winkler foundation is used to verify the the simulation model. Experimental test rig with testing data is used to further verify the simulation model. Swinging load speed threshold is found from the simulation, which will prevent the crane's stress and crane tippingfailures.